PELAKSANAAN PERJANJIAN BAGI HASIL TANAH PERTANIAN PADI DI KECAMATAN RANGSANG BARAT KABUPATEN KEPULAUAN MERANTI - Suhani, Muhammad; Warman, Kurnia; Ferdi, Ferdi (Universitas Ekasakti, 2023)
The purpose of this study was to determine and analyze the agricultural land production sharing agreement system that applies in Rangsang Barat District. What are the influencing factors in determining the choice of the implementation system for the Production Sharing agreement? As well as the legal consequences arising from the implementation of the agreement for the results of agricultural land in Rangsang Barat District, Islands Regency. The research method used is an empirical juridical approach. Then the data collected were analyzed qualitatively. From the results of the research, it was found that the implementation of the rice farming yield sharing agreement carried out in Rangsang Barat District, Islands Regency was not by Law Number 2 of 1960 concerning Production Sharing Agreements so the implementation of the rice farming production sharing agreement had not gone well. good and not effective.